Mechanisms and molecular approaches for heat tolerance in rice (Oryza sativa L.) under climate change scenario - Syed Adeel Zafar; Amjad Hameed; Muhammad Amjad Nawaz; Wei MA; Mehmood Ali Noor; Muzammil Hussain; Mehboob-ur-Rahman (Journal of Integrative Agriculture, 2018)
Rice, a staple cereal crop in many parts of the world, has been confronted with multiple environmental stresses including high temperature, negatively impacts the booting as well as anthesis growth stages. The situation is further complicated by the changing climatic conditions, resulting in gradual escalation of temperature as well as changing the rainfall pattern and frequency, thus raising a concern of food security worldwide. The situation can be combat by developing rice varieties with excellent genetics with improved morpho-physiological, biochemical, and molecular mechanisms, together can minimize the adverse effects of heat stress. Here, several strategies (encompassing genetic and genomic, and mechanisms involved) for mitigating the impact of high temperature on rice have been discussed. Finally, the utilization of genomic knowledge in augmenting the conventional breeding approaches have been comprehensively elaborated to develop heat tolerant germplasm.